Perovskite cathodes for NaBH4/H2O2 direct fuel cells - Santos, D M F
Perovskite type oxides are evaluated as cathodes for hydrogen peroxide (H2O2) reduction in direct borohydride fuel cells (DBFCs). The study is conducted on button type ceramic electrodes of LaCoO3 (LC), La0.84Sr0.16CoO3 (LSC), La0.8Sr0.2Fe0.8Co0.2O3 (LSFC), and La0.7Sr0.3MnO3 (LSM), thus avoiding cross contributions of carbon or nickel catalyst supports. Cyclic voltammetry shows that LSM has the highest activity for H2O2 reduction in alkaline solution, with the other three materials showing minimal (LC) to none (LSC, LSFC) electroactivity. The data also suggest that only LC and LSM are stable within the tested potential window, although the alteration of the samples surface is apparent in scanning electron microscopy images collected after the electrochemical measurements. The analysis of LSM by chronopotentiometry in light of the Sand equation indicates ca. 1 electron involved in the H2O2 reduction. A demonstration DBFC employing a single phase LSM ceramic cathode yields a peak power density of 8.2 mW cm 2 at 28 mA cm 2, at 45 C. This value is about 60% of that obtained with a commercial platinum foil electrode, which is a notable feature and demonstrates the potential of LSM as an alternative low cost cathode for DBFCs